2019
DOI: 10.4251/wjgo.v11.i9.705
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-331 inhibits development of gastric cancer through targeting musashi1

Abstract: BACKGROUNDThe molecular mechanisms involved in microRNAs (miRNAs) have been extensively investigated in gastric cancer (GC). However, how miR-331 regulates GC pathogenesis remains unknown.AIMTo illuminate the effect of miR-331 on cell metastasis and tumor growth in GC.METHODSThe qRT-PCR, CCK8, Transwell, cell adhesion, Western blot, luciferase reporter and xenograft tumor formation assays were applied to explore the regulatory mechanism of miR-331 in GC.RESULTSDownregulation of miR-331 associated with poor pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…miR-331 has also been reported to be a tumor suppressor in glioblastoma, which inhibited cell proliferation and clonogenic growth [31]. In gastric cancer, miR-331 was associated with poor prognosis and inhibited cell proliferation, metastasis, and tumor growth by targeting MSI1 [12]. The downregulation of miR-331 significantly affected the progression of ovarian cancer by targeting RCC2 [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-331 has also been reported to be a tumor suppressor in glioblastoma, which inhibited cell proliferation and clonogenic growth [31]. In gastric cancer, miR-331 was associated with poor prognosis and inhibited cell proliferation, metastasis, and tumor growth by targeting MSI1 [12]. The downregulation of miR-331 significantly affected the progression of ovarian cancer by targeting RCC2 [27].…”
Section: Discussionmentioning
confidence: 99%
“…miR-455-5p and miR-1255a were upregulated with poor overall survival, while the overexpression of their target genes was related to a good overall survival, which indicated the potential roles of mir-455-5p and miR-1255a in the therapy of breast cancer [10]. miR-331 is upregulated in breast cancer, and it has been demonstrated to be dysregulated in many other cancers, such as lung cancer, gastric cancer, and prostate cancer [11][12][13][14][15]. In gastric cancer, miR-331 was downregulated, which inhibited the cell proliferation, metastasis, and tumor growth of gastric cancer [12].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, Yang et al pointed out that upregulation of MSI1 weakened the anti-cancer role of miR-331 in gastric cancer. 51 Gao et al stated that MSI1 was highly expressed in colon cancer tissues, and its downregulation inhibited the growth of colon cancer by targeting p21cip1. 52 Moreover, Araujo et al revealed that MSI1 could affect radioresistance via controlling DNA-protein kinase catalytic subunit in glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Gu et al found that the recurrence rate of esophageal adenocarcinoma patients with high-expressing serum miR-331-3p was lower, and miR-331-3p could be a potential biomarker for predicting tumor recurrence in patients with esophageal adenocarcinoma [25]. Yang et al found that miR-331-3p inhibits the development of gastric cancer by targeting MSI 1 and serve as an indicator of gastric cancer prediction and prognosis [26]. Novel targets of miR-331-3p for liver cancer were also revealed.…”
Section: Introductionmentioning
confidence: 96%